Madness in international relations psychology, security, and the global governance of mental health - Howell, Alison (Interventions (Routledge (Firm), 2011)
"Madness in International Relations provides an important and innovative account of the role of psychology and psychiatry in global politics, showing how mental health governance has become a means of securing various populations, often with questionable effects.Through the analysis of three key case studies Howell illustrates how such therapeutic interventions can at times be coercive and sovereign, at other times disciplinary, and at still other times benevolent, though not benign. In each case a diagnostic competition is traced, that is, a contestation over how best to diagnose and treat the population in question. The book examines the populations of Guantanamo Bay, post-conflict societies and western militaries, identifying how these diagnostic competitions ultimately rest on shared assumptions about the value of psychology and psychiatry in managing global security, about the value of achieving security through mental health governance, and ultimately about the medicalization of security.This work will be of great interest to all scholars of International relations, critical theory and security studies"--Provided by publisher.